Engagement as Positioning Resource in The Evaluative Language of Malay Newspaper Discourse - Suhaini Sarikon; Roksana Bibi Abdullah (LingPoet: Journal of Linguistics and Literary Research, 2026)
This article delves into the exploration of Evaluative Language Theory particularly the concept of Engagement as positioning resource within the discourse of Malay newspaper. Two types of newspapers were used in this study: Berita Harian/Berita Minggu Singapura (BH/BM S’pura) and Berita Harian/Berita Ahad Malaysia (BH/BA M’sia). Only commentary articles were selected as study materials, ensuring they were related to the bombing of the World Trade Center in New York that occurred on September 11, 2001. This study is limited to articles with such themes due to their similar context. The study explores the strategies employed by newspapers through their commentators to influence readers, enabling the newspapers to instill the propositions they aim to advance within the readers. This description is based on analytical findings regarding Engagement in Malay newspaper discourse contained within the texts. The study is grounded in Systemic-Functional Linguistics as a linguistic framework for examining the Engagement system present in Malay language newspaper discourse. Engagement consists of types such as monogloss and heterogloss. The concept of Evaluative Language in Malay newspaper discourse can be explained by outlining these types of Engagement.